Surrogate Advertisements as Mediator between Celebrity Endorsement, Core Product Perception and Consumer Purchase Intention in Nepal - Sajeeb Kumar Shrestha; Aayush Pokhrel; Sanket Shrestha; Dasarath Neupane; Dipak Mahat (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
The aim of this study is to investigate surrogate advertisement as mediator between celebrity endorsement, core product perception and consumer purchase Intention. This study used a descriptive and causal research design to present the information and to test the direct and indirect relationships among the constructs of the study. The research population comprised of people from Kathmandu City the biggest city of Nepal and a mini-Nepal. Structured questionnaires were administered through a field survey, and data were gathered from 150 samples. The data was analysed and hypotheses tested through reliability analysis, descriptive statistics, correlation analysis, multiple regression analysis and mediation analysis. The research findings suggest that surrogate advertising is an important tool to increase consumer purchase intention through the effects of celebrity endorsement and core product image. The results offer valuable insights for future marketing strategies, allowing firms to work around the regulatory barrier while enhancing consumer involvement.